2004
DOI: 10.1111/j.1365-2036.2004.01969.x
|View full text |Cite
|
Sign up to set email alerts
|

Elemental diet modulates the growth of Clostridium difficile in the gut flora

Abstract: Summary Background and aims : Tube feeding is regarded as a risk factor for Clostridium difficile‐associated diarrhoea. Recently, we reported that C. difficile toxin was frequently found in patients receiving an elemental diet. The present study was conducted to clarify whether elemental diets are associated with the growth of C. difficile in the gut flora. Methods : C. difficile was cultured for 72 h in various concentrations of elemental diet containing 3% thioglycollate, and the growth rate or activity of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…Therefore, it is difficult to predict the prevalence rate of C. difficile in healthy human gut microbiota correctly by the conventional PCR using DNA templates extracted by phenol-chloroform procedure since copy numbers of C. difficile in the healthy human gut microbiota are estimated to be very small. However, in a part of our recent study we showed that C. difficile toxin B mRNA was detected in half of 10 fecal samples by reverse transcription polymerase chain reaction (RT-PCR) using glass powder (2), which can eliminate PCR inhibitors in feces (6). In the present study, we attempted to confirm the validity of the results of RT-PCR using a larger number of fecal samples and clarify the true prevalence rate of C. difficile in healthy human gut microbiota.…”
mentioning
confidence: 99%
“…Therefore, it is difficult to predict the prevalence rate of C. difficile in healthy human gut microbiota correctly by the conventional PCR using DNA templates extracted by phenol-chloroform procedure since copy numbers of C. difficile in the healthy human gut microbiota are estimated to be very small. However, in a part of our recent study we showed that C. difficile toxin B mRNA was detected in half of 10 fecal samples by reverse transcription polymerase chain reaction (RT-PCR) using glass powder (2), which can eliminate PCR inhibitors in feces (6). In the present study, we attempted to confirm the validity of the results of RT-PCR using a larger number of fecal samples and clarify the true prevalence rate of C. difficile in healthy human gut microbiota.…”
mentioning
confidence: 99%
“…Bliss, et al (13), encontraron que su uso, especialmente de sondas colocadas más allá del píloro, se relacionaba con un mayor riesgo de enfermedad asociada a C. difficile (20 % Vs. 8 %). Algunas explicaciones de estos hallazgos serían el uso limitado de fórmulas elementales, las cuales se han relacionado con la infección por este germen debido a la alteración de la flora intestinal del colon (34,35), y el poco uso de sondas en el yeyuno para nutrición entérica, las cuales se han relacionado más con la infección por este microorganismo (13). Infortunadamente, no se pudieron recopilar datos sobre el tipo de sonda utilizada para la nutrición de los pacientes.…”
Section: Discussionunclassified
“…Thus, the C. difficile strain itself, including its capacity for toxin production (36) and spore formation and its counts in the colon, could be important. In addition, host factors, such as the levels of nutrients in the gut content crucial to the regulation of toxin production (13,14) and immunity, including preexisting and formation of new toxin-neutralizing antibodies, may contribute to the outcome of therapy for CDAD and the elimination of C. difficile (20,31,37).…”
Section: Discussionmentioning
confidence: 99%